Irrational Thoughts and Their Relationship to Emotional Stability for The Elderly in Jericho Governorate - halabiyah, Fadwa Abdallah; Saeed, Marwan Fakhry (Journal of Educational and Psychological Sciences, 2021)
The aim of this study was to determine the level of irrational thoughts and emotional stability among the elderly in Governorate of Jericho, as well as the relationship between them based on gender, economic level, accommodation type, and educational level. The descriptive-analytical approach, the irrational thoughts scale, and the emotional stability scale were employed to achieve these objectives. The sample included (300) elderly people, males and females, who were chosen randomly from the elderly attending the social development centers and Grandparents’ House in Jericho. Cronbach Alpha, Pearson Correlation coefficient, t- test, one-way ANOVA were calculated using the Statistical Package for Social Sciences (SPSS). The results of this study revealed that the elderly in Jericho Governorate have a moderate degree of both irrational thoughts and of emotional stability. The results also demonstrated an inverse statistically significant relationship between irrational thoughts and emotional stability among the elderly. The results also showed no differences in the level of irrational thoughts among the elderly in the Jericho governorate due to the variables of gender or economic level. It was found that there were differences in the level of irrational thoughts due to accommodation type and educational level. The results showed that there were no differences in the level of emotional stability among the elderly based on gender, economic level, or accommodation type, while there are statistically significant differences in the level of emotional stability attributed to the educational level.
Keywords: Irrational thoughts; elderly; emotional stability; the Governorate of Jericho